Pengaruh Return On Equity (Roe), Reputasi Underwriter, Financial Leverage Terhadap Undepricing Initial Public Offering (Studi Empiris Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia pada Tahun 2018-2020) - Dakhi, Semarni; Chandrayanti, Teti; Yuli Ayu Putri, Sri (Fakultas Ekonomi, Universitas Ekasakti, 2024)
This study aims to determine whether Return On Equity, Underwriter Reputation and Financial Leverage have an effect on Undepricing Initial Public Offering in Mining Companies Listed on the Indonesia Stock Exchange in 2018-2020, either partially or simultaneously. The data collection method used in this research is literature review and web review and the type of data used in this research is quantitative data. The population of this research is 47 mining companies. The sample in this study used purposive sampling technique, so that the sample in this study amounted to 14 companies. The data analysis technique is multiple linear regression. The results of this study indicate that: 1) Return on Equity has a significant effect on Undepricing Initial Public Offering, it can be seen that the t-count value is 4.441 > t-table 2.024 and the significance is 0.000 <0.05. 2) Underwriter reputation has a significant effect on Undepricing Initial Public Offering, it can be seen that the t-count value is 3.273 > t-table 2.024 and the significance is 0.041 <0.05. 3) Financial Leverage has a significant effect on Undepricing Initial Public Offering, this can be seen from the t-count value of 3.726 > t-table 2.024 and the significance of 0.001 <0.05. 4) Return on Equity, Underwriter's Reputation and Financial Leverage simultaneously affect the Undepricing Initial Public Offering, this can be seen from the f-count 11.381 > t-table 2.85 and the significance is 0.000 <0.05.